Analysis Of Factors Which Affect Cafe Customer Loyalty Post Covid-19 Pandemic Using Structural Equation Modeling - Lutecia, Ekacandra; Suryadi , Kadarsah (Ridwan Institute, 2024)
One of the MSME business sectors that is most popular and frequently visited by Indonesian people is cafes. In December 2019, the global health crisis caused by the Coronavirus disease (COVID-19) began to hit, causing the world to be caught unprepared and to disrupt business activities, one of which is the cafe sector. To encourage people to visit cafes and increase revenue, further research is needed regarding factors that can increase customer purchasing power through customer loyalty. This study took data from online respondents to see their perceptions of the factors that influence customer loyalty for cafe visitors in the Greater Jakarta area. The results of distributing this questionnaire were then processed using Structural Equation Modeling (SEM). From this study it was found that customer satisfaction has the most influence on customer loyalty, which is then followed by trust and customer engagement. It was also found that service quality has a direct effect on customer loyalty. Atmosphere & environment has an indirect effect on customer loyalty. However, brand image, employee attitude, price and product quality were found to have no effect on customer loyalty.